KNOWLEDGE, ATTITUDE, SPIRIT OF VOLUNTEERISM AND SELF-ESTEEM AMONG STUDENTS IN A PUBLIC UNIVERSITY - Sham, Fatimah; Azamuddin, Ain Aqiela; Ismail, Amirah; Zulkifli, Nur Nadhirah; Mohd Bahar, Nur Ermarina Aida; Isa, Badrul; Ariff, Muhammad Hamizan (Journal of Islamic, Social, Economics and Development, 2024)
Volunteerism is integral to co-curricular activities in universities, playing a pivotal role in enhancing students' personal growth. This study investigated volunteerism among 1,161 undergraduate students from three major campuses of a public university in Malaysia, focusing on their levels of knowledge, attitudes, spirit towards volunteerism, and self-esteem. Using a descriptive cross-sectional design and data collected through self-administered questionnaires, the study assessed various dimensions of volunteerism and its impact. The analysis, conducted using SPSS Version 21, revealed that 53.7% of respondents were occasional volunteers, with 76.1% demonstrating a positive spirit towards volunteerism. A majority exhibited high knowledge (58.1%) and positive attitudes (82.5%) and reported high self-esteem (60.9%). Significant associations were found between the levels of knowledge, attitudes, and spirit towards volunteerism and self-esteem, indicating that greater involvement and positive perceptions of volunteerism are linked to higher self-esteem. These findings suggest that university students generally possess a strong commitment to volunteerism, underscoring the need for enhanced communication strategies by the Ministry of Higher Education and universities to foster greater participation and awareness of volunteer opportunities